Acupuncture Treatment for Post-Stroke Aphasia at Harvest City Therapy Center in Bogor - Lai Monica Pei Su; Chantika Maadini; Amal Prihatono; Puspo Wardoyo (Jurnal Indonesia Sosial Sains, 2026)
Aphasia is a communication disorder that often occurs in post-stroke patients due to damage to the language centers in the brain. This condition can impair the ability to speak, understand language, and interact with the environment. Therefore, therapy is needed to help restore communication function, one of which is acupuncture. This study aimed to determine the effectiveness of acupuncture therapy in improving communication skills in elderly post-stroke aphasic patients. The method used was a case study, with several sessions of acupuncture therapy administered. Assessment was conducted through observation of the patients' communication skills, including verbal expression, language comprehension, responses, and social interaction. The study results showed improvements in communication skills after acupuncture therapy. Patients demonstrated improvements in expressing simple words, understanding instructions, and responding better. Social interactions also improved, indicated by more active engagement in communication. The conclusion of this study shows that acupuncture therapy has the potential as a complementary therapy in supporting the recovery of communication function in elderly aphasia patients after stroke.